The sustainability of shariah-compliant status: capital structure of Malaysian property Companies / Nurqystina Sofea Rozaimi and Ummi Diyana Ahmad - Rozaimi, Nurqystina Sofea; Ahmad, Ummi Diyana (Arshad Ayub Graduate Business School, 2018)
Shariah-compliant Listed Property Companies (LPCs) perhaps has different preference in making a decision on the company’s capital structure. This is to ensure the companies comply with the screening benchmark stated by Shariah Advisory Council (SAC) of the Securities Commission of Malaysia (SC). This study uses the regression of random effects models to identify the capital structure determinants and seeks if there are differences in capital structure between sustainable Shariahcompliant LPCs and non-sustainable Shariah-compliant LPCs in Malaysia. The sample consists of twenty-six (26) and forty-six (46) companies for sustainable Shariah-compliant LPCs and non-sustainable Shariah-compliant LPCs respectively. This study uses panel data which focusing on the five (5) year period between 2013 to 2017. There are three (3) models use in this study in order to achieve the research objectives, which are Model A (sustainable Shariah-compliant LPCs), Model B (nonsustainable Shariah-compliant LPCs) and Model C (all Shariah-compliant LPCs). Leverage as a dependent variable of this study while profitability, growth, liquidity, tangibility and size as independent variables. All independent variables significantly influence leverage except for size in the Model A. The findings indicate the Shariahcompliant LPCs must consider profitability, growth, liquidity, and tangibility in managing leverage of their companies to ensure they are not exceeding the thirty-three (33) percent benchmark set by SAC of SC. This study discovers that the result, lean towards the pecking order theory rather than trade-off theory. Surprisingly, this study reveals that there is no significant difference in the capital structure of sustainable and non-sustainable Shariah-compliant LPCs. The study is capable to provide information for property companies, especially Shariah-compliant LPCs in managing their leverage level. This study also gives insight to Shariah-compliant LPCs in Malaysia, especially for those who intend to maintain their Shariah status.